Rutters, Courses and Voyages: Navigation at sea in north-west Europe in the fifteenth century. Issue 1 (2nd January 2023) - Rose, Susan
Abstract : Much of the discussion of how mariners set and followed a course across the seas around north- west Europe has focused on the few surviving manuscript rutters. These are best described as an early form of pilot book. Very few now exist; it is generally supposed because of the conditions in which they were used at sea. Similarly, there are few accounts of medieval voyages in these waters which contain any information about navigation or in fact any other technical details of the sea passage. The most frequent descriptions found in these accounts are of heroic survival in a terrifying storm, leading to the suspicion that this was something almost expected by anyone reckless enough to go to sea, a form of 'must-have' experience. This article explores whether these circumstances can offer anything useful about navigational practice in the fifteenth century by looking both at the surviving rutters and the accounts of voyages. It is argued that careful study of these sources and comparison between them allows us to draw the conclusions that rutters were very useful in setting out the best course to follow but more as aides memoire in port than as guides when at sea.